2017
DOI: 10.1186/s12974-017-0914-6
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemic stroke and the recanalization drug tissue plasminogen activator interfere with antibacterial phagocyte function

Abstract: BackgroundStroke induces immune alterations such as impaired oxidative burst and reduced release of neutrophil extracellular traps (NETs). We hypothesised that key enzymes of these defence mechanisms may be altered in ischaemic stroke. Therefore, we analysed the intra- and extracellular amounts of myeloperoxidase (MPO) and neutrophil elastase (NE) in patient sera and granulocytes and monocytes. Because the autonomous nervous system is thought to mediate stroke-induced immune alterations, we also studied the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Because neutrophil degranulation can also result in rapid release of neutrophil serine proteases from azurophilic granules into the extracellular medium and circulation, we measured the level of circulating neutrophil elastase. Consistently with previous data, 20 serum neutrophil elastase levels were significantly higher in patients with IS than HCs (figure 1C).…”
Section: Resultssupporting
confidence: 93%
“…Because neutrophil degranulation can also result in rapid release of neutrophil serine proteases from azurophilic granules into the extracellular medium and circulation, we measured the level of circulating neutrophil elastase. Consistently with previous data, 20 serum neutrophil elastase levels were significantly higher in patients with IS than HCs (figure 1C).…”
Section: Resultssupporting
confidence: 93%
“…Our findings in real-world practice could be explained by early improvement in stroke severity (including level of alertness and dysphagia) in those with faster door to needle times. Another possible explanation is that immunosuppression induced by thrombolysis with tissue plasminogen activator, might potentially increase the susceptibility to SAP with treatment later rather than earlier in the thrombolysis time window ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…In IS, DAMPs and other lifesaving signals released from the dying cerebral tissues trigger intracytoplasmic granules in mounting neutrophils to translocate to the phagosomes and to the plasma membrane, which resultantly makes NSPs detectable in the plasma of IS patients. In line with it, a study reported that serum NE level in AIS patients was signi cantly altered compared to controls [34]. A recent clinical study enrolled 41 AIS patients and matched healthy controls reported that plasma NE levels were signi cantly increased in AIS patients compared to controls, and NE levels were associated with stroke severity [10].…”
Section: Discussionmentioning
confidence: 82%